Chemical composition of gliricidia silage subjected to different ensilion soots (Research, Society and Development, 2021)
The objective of this study was to evaluate the chemical characteristics of gliricidia silage as a function of different ensilion sorrities. The first cut of the plants was made one year after planting, at the height of 50 cm from the soil surface. The silages were distributed in a completely randomized experimental design with four units per treatment (microsilos) with four repetitions. It was decided by fermentation period of the silage of sixty days. The treatments consisted of five different silage processes: T1 – gliricidia consorcised with sorlum (30%, 40% and 50% of the weight of green matter); T2 - gliricidia conorted with citrus pulp (30%, 40% and 50% of the weight of green matter); T3 - gliricidia enurchecidal in greenhouse considering (two, three and four hours); T4 - gliricidia in natura and T5 - gliricidia concrophernated with ground corn (30%, 40% and 50% of the weight of green matter). It was concluded that gliricidia demonstrated that it is a legume that alters its chemical characteristics according to the consorciation used during the silage process.